تحليل أداء نظام إدارة المحرِّك البنزيني باستخدام برنامج تكنولوجيا السَّيارات (Damascus University Journal for engineering sciences, 2023)
Recent years have witnessed a remarkable development in the electronic control systems used in cars, especially the petrol engine management system, which plays a prominent role in improving the performance of the engine, and in reducing fuel consumption and the harmful exhaust gases to the minimum limits. The main objective of this research is to study the performance of the petrol engine management system using the famous simulation program" Automotive Technology". In general, the main task of the management system is to precisely control the fuel injection and the timing of the ignition spark simultaneously. In this case, the management system consists of a pre-programmed electronic control unit, in addition to a set of sensors that determine the input variables, and a set of actuators that implement the output variables.The input variables include: engine speed, engine load, engine temperature, throttle opening angle, in addition to the data received about the percentage of oxygen in the exhaust gases on the one hand, and the knock phenomenon on the other hand. As for the output variables, they include: the ignition timing angle φign , the dwell period dw, and the fuel injection time tf . The simulation results showed the influence of the input variables on the output variables when the car is working in different operating conditions including: engine cold start, warm-up, idle speed, acceleration and deceleration. The range of numerical values ​​for the different output variables was also obtained as follows: φign = [10° - 50º]; dw = [25 - 46]%;  tf =[ 1 - 10] msFinally, for future studies,  this research suggests studying of EGR  control system .
Keywords: petrol engine; engine management system; automotive technology; simulation; sensors; actuators; control unit; input variables; output variables; ignition timing angle; dwell period; fuel injection time